Pengaruh Pemasaran Digital dan Ulasan Pelanggan Online terhadap Keputusan Pembelian Produk Skincare Glad2Glow di TikTok Shop - Nursafrina; Amirulmukminin; Intisari Haryanti (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
This study aims to analyze the influence of digital marketing and online customer reviews on purchasing decisions for Glad2Glow skincare products on the TikTok Shop platform. The research employs a quantitative associative approach, collecting data through Likert-scale questionnaires from 100 student respondents in Bima City selected using purposive sampling. Data analysis was conducted using multiple linear regression with SPSS, preceded by validity, reliability, and classical assumption tests. The results reveal that partially, digital marketing has no significant effect on purchasing decisions (β = -0.005; sig = 0.968), while online customer reviews have a positive and significant effect (β = 0.226; sig = 0.002). Simultaneously, both variables contribute to purchasing decisions, with a coefficient of determination (R²) of 0.502, indicating that 50.2% of the variance in purchasing decisions is explained by the model. The findings highlight the dominant role of customer reviews in shaping consumer trust and influencing buying behavior. The implication of this study suggests that businesses should prioritize the management of customer reviews and enhance digital engagement strategies to effectively drive purchasing decisions in e-commerce environments.